(untitled) (Web of Teachers: Inderscience Research, 2025)
The article examines the main role of modern digital technologies in the world economy. Digitalization is seen as a key factor in increasing the efficiency of production processes, improving product quality, reducing costs and increasing the competitiveness of enterprises. Particular attention is paid to digital transformation in the industrial sector, using it as a means to increase productivity and introduce innovation. The article analyzes the concepts of "digitalization", "digital transformation" and "digital organization", and provides economic essence and interdependence. The article also describes the stages of introduction of digital technologies in enterprises and their main types.